Caused-Motion Verbs in the Middle English Intransitive Motion Construction - Huber, Judith (Variation and Change in the Encoding of Motion Events, 2013)
Based on an analysis of more than 300 Middle English verbs attested in the intransitive motion construction, this chapter shows that among them, different from Present-Day English, there is a surprisingly high proportion of verbs that are primarily verbs of caused motion, such as throuen ‘throw’. I argue here that the sporadic intransitive motion use of these verbs may be explained by a number of formally and semantically similar patterns in which both intransitive and caused-motion verbs occur. These include be + past participle and the combination with a reflexive pronoun. These patterns form a closely-knit family of constructions tending to blur the distinction between the two types of verbs.
Keywords: construction grammar; Middle English; reflexive pronoun; transitivity; verb of motion

English Historical Linguistics 2008: Selected Papers from the Fifteenth International Conference on English Historical Linguistics (ICEHL 15), Munich, 24–30 August 2008. Volume I: The History of English Verbal and Nominal Constructions - Lenker, Ursula; Huber, Judith; Mailhammer, Robert (John Benjamins, 2010)
The fourteen studies selected for this volume – all of them peer-reviewed versions of papers presented at the 15th International Conference on English Historical Linguistics 2008 (23–30 August) at the University of Munich – investigate syntactic variation and change in the history of English from two perspectives that are crucial to explaining language change, namely the analysis of usage patterns and the social motivations of language change. Documenting the way syntactic elements have changed their combinatory preferences in fine-grained corpus studies renders the opportunity to catch language change in actu. A majority of studies in this book investigate syntactic change in the history of English from this viewpoint using a corpus-based approach, focusing on verbal constructions, modality and developments in the English noun phrase. The book is of primary interest to linguists interested in current research in the history of English syntax. Its empirical richness is an excellent source for teaching English Historical Syntax.

Graeme Trousdale and Elizabeth Closs Traugott (2013). Constructionalization and Constructional Changes. Oxford: Oxford University Press - Huber, Judith (2016)

Introduction: Capturing and explaining syntactic change in the history of English - Lenker, Ursula; Huber, Judith; Mailhammer, Robert (English Historical Linguistics 2008: Selected papers from the fifteenth International Conference on English Historical Linguistics (ICEHL 15), Munich, 24-30 August 2008.. Volume I: The history of English verbal and nominal constructions, 2010)

Motion and the English Verb. A Diachronic Study - Huber, Judith (Oxford University Press, 2017)
In Motion and the English Verb, a study of the expression of motion in medieval English, Judith Huber provides extensive inventories of verbs used in intransitive motion meanings in Old and Middle English, and discusses these in terms of the manner-salience of early English. Huber demonstrates how several non-motion verbs receive contextual motion meanings through their use in the intransitive motion construction. In addition, she analyzes which verbs and structures are employed most frequently in talking about motion in select Old and Middle English texts, demonstrating that while satellite-framing is stable, the extent of manner-conflation is influenced by text type and style. Huber further investigates how in the intertypological contact with medieval French, a range of French path verbs (entrer, issir, descendre, etc.) were incorporated into Middle English, in whose system of motion encoding they are semantically unusual. The various cognitive and contact-linguistic aspects of their integration into Middle English are studied in an innovative approach which analyzes their usage contexts in autonomous Middle English texts as opposed to translations from French and Latin. Huber explains how these verbs were initially borrowed not for expressing general literal motion, but in more specific, often metaphorical and abstract contexts. Her study is a diachronic contribution to the typology of motion encoding, and advances research on the process of borrowing and loanword integration.
Keywords: motion verb; motion encoding typology; intransitive motion construction; construction grammar; Old English; Middle English; medieval French; language contact; borrowing; path verb; manner verb

"No man entreth in or out": How are typologically unsuitable loanverbs integrated into English?” - Huber, Judith (English Historical Linguistics 2010. Selected Papers from the Sixteenth International Conference on English Historical Linguistics (ICEHL 16), Pécs, 23-27 August 2010, 2012)
English motion verbs typically encode the manner of motion (e.g. run, walk, cf. e.g. Talmy 2000: 27, Slobin 2004). This raises the question of how French- and Latin-borrowed motion-verbs such as enter, descend, that express the path of motion and therefore are typologically ‘unsuitable’ for English, are integrated into this language. Based on a detailed analysis of the occurrences of enter in PPCME2 and CEECS, and drawing on ideas from studies in second language acquisition and cognitive linguistics, it will be shown that on the one hand, enter has a strong tendency to be used non-literally, i.e. for situations where the figure or goal are not concrete or visually perceivable; in its literal uses, on the other hand, it will be argued to bear additional manner-meaning. Both findings can be explained by the verb being a semantic misfit among English motion verbs. Similar usage patterns will be shown to apply to other borrowed path-verbs.

Richard Ingham, ed. (2010) The Anglo-Norman Language and its Contexts. York: Medieval Press in assoc. with The Boydell Press - Huber, Judith (2011)

Stefan Thim (2012) Phrasal Verbs. The English Verb Particle Construction and its History. Topics in English Linguistics 78. Berlin/Boston: de Gruyter Mouton - Huber, Judith (2014)

The early life of borrowed path verbs in English - Huber, Judith (Motion and Space across Languages. Theory and applications, 2017)
In the Middle English period, a number of pure path verbs (e.g. enter, issue, descend, ascend) were borrowed from French and Latin into English. An analysis of the Old and Middle English motion verb inventory reveals that before this, pure path verbs hardly existed; an analysis of c. 1,000 Old and Middle English motion descriptions shows that path information is typically expressed outside the verb. The borrowed path verbs are therefore a new pattern in the Middle English system of talking about motion. By comparing their use in autonomous Middle English texts and in texts translated from French or Latin, I show that in autonomous texts, they are more restricted to non-literal motion (such as ‘descend from one’s ancestors’) and to specific types of literal motion, while in the translations, they are more freely used for general literal motio
Keywords: borrowing; Middle English; Old English; translation